New Association rule mining on multiband satellitic image data - Hai-hui Wang; Min Ren (2008 Chinese Control and Decision Conference, 2008)
Association rule mining is one of the most important problems of data mining. Since multi-band image data contains huge amounts of information, itpsilas a very potent area to discover useful rules. Compared to traditional market ldquobasket datardquo, multiband satellitic image has specific characteristics and also presents specific difficulties. Two problems need to be solved to apply association rule mining on multiband satellitic images. The first is to deal with quantitative attributes. The second is to efficiently handle huge quantities of information. For the first problem, partitioning quantitative data into intervals is a simple but effective way. For the second problem, we propose a new approach based on transaction patterns and occurrences counting, which simplifies the calculation of support and is much more efficient. A modified apriori algorithm is given for which performance analysis shows obvious improvements.